الفرائد الواردة في سياق الحديث عن الإعراض عن القرآن الكريم: دراسة دلالية وصفية - عثمان، محمود علي عثمان (جامعة الوصل, 2021)
يهدف البحث إلى الكشف عن ظاهرة التمكن الدلالي للفرائد القرآنية الواردة في سياق الحديث عن القرآن الكريم، وهي ظاهرة تعكس إعجازه البياني في أسلوبه، ولتحقيق هذا الهدف فقد سلك الباحث المنهج التحليلي اللغوي، والمنهج الوصفي، وخلصت الدراسة إلى أن فظاهرة التمكن الدلالي للفرائد القرآنية ترتبط بالعلاقات بين البنى المتوالية للسورة- الواردة فيها الفريدة- بأكملها على وفي مناسبة دلالة الفريدة معجميا، لسياقها الذي استدعاها، وهاتان العلاقتان مجتمعتان مكنتا الفريدة دلاليا من التفرد في سياقها بحيث تؤدي المعنى المراد كله بدقة ولا يغني غيرها من مرادفاتها غناءها، ليثبت بذلك بناؤها واتساقها الفني وفيضها المتجدد من الظلال والمعاني والدلالات التي تتسع وتنمو وتفيض وتتجدد بتدبر هذه الفرائد، وأوصت الدراسة بمواصلة رصد ظاهرة التمكن الدلالي للفرائد القرآنية الواردة في موضوعات أخرى، وتجديد قراءتنا للقرآن الكريم ومدارسته بما يحقق تدبره.
The purpose of the research is to highlight the phenomenon of the semantic mastery of the Quranic uniques in the context of the Holy Quran, a phenomenon that reflects its graphic miracles in its style and aims to reveal its significance to the purposes of the Holy Quran and its Surah’s, to achieve the aim of the study: the researcher used the linguistic analytical method and the descriptive method, the study concluded in its results to phenomenon of the artistic semantic consistency of the Qur’anic authors is related to the relations between the successive structures of the surah - in which the unique - whole is presented according to: a unique and lexical connotation of the context in which they were called, the purpose of the sura and the purposes of the Qur’an, so that the meaning of the whole meaning accurately and does not enrich other synonyms singing, to prove the building and artistic consistency and its renewed flow of shadows and meanings and meanings that expand and grow and overflowing and renewed by meditating in these uniques, the study recommended the continuation of monitoring the phenomenon of semantic mastery of Quranic Uniques mentioned in other subjects and renewal of our reading of the Holy Quran and study it to achieve its meditation.
Keywords: القرآن الكريم -- الفرائد القرآنية -- الإعجاز اللغوي -- السياق القرآني